Indications and need for neuroimaging and newer developments in brain imaging in mild head injury - Muthukumar, N. (Indian Journal of Neurotrauma, 2005)
Mild head injury (MHI) accounts for over 80% of hospital attendance due to head injury. However, there is no consensus in the evaluation and management of patients with MHI. The aim of this article is to provide an overview of the indications and need for neuroimaging in MHI as well as the evolving role of newer imaging modalities in the evaluation and management of MHI. The current evidence in the literature does not support the routine use of plain radiography of the skull in the evaluation of patients with MHI. The prevalence of intracranial lesions in MHI varies from 5% in GCS 15 to 40% in GCS 13. Several groups have proposed various guidelines for the evaluation and management of MHI patients. These include: NICE guidelines, New Orleans CT head rule, Canadian CT Head rule, Italian Guidelines, Scandinavian Guidelines, EFNS (European Federation of Neurosurgical Societies) guidelines, and WHO guidelines. Most of these guidelines are applicable only to adult patients. Separate guidelines have been provided by the American Academy of Pediatrics for children less than 2 years of age and for those between 2 and 20 years of age. However, recent studies have shown that none of these guidelines have 100% sensitivity. Therefore, physicians who use these guidelines should be aware of the small risk of missing intracranial lesions in patients with MHI. Newer imaging modalities like newer MR sequences, MR spectroscopy, Magnetic Source Imaging (MSI), PET, and SPECT have provided objective evidence of structural and functional alterations in patients with MHI even when CT and routine MR sequences do not reveal abnormalities. Thus, these imaging techniques have been shown to have a role in the evaluation of patients with persistent post-concussive symptoms and they have provided proof of organic basis for these symptoms.
Keywords: Computed tomography; Glasgow Coma Scale; Magnetic resonance imaging; mild head injury; minor head injury; PET; SPECT